Differences in glance behavior between drivers using a rearview camera, parking sensor system, both technologies, or no technology during low-speed parking maneuvers. (February 2016) - Kidd, David G.; McCartt, Anne T.
Highlights: Driver glance behavior was coded during four low-speed parking maneuvers. Drivers had a camera, a sensor system, both, or neither technology. The presence of a camera and/or sensor system changed glance behavior. Drivers with cameras used mirrors less than those without cameras. Drivers with both technologies used the camera less than those with a camera. Abstract: This study characterized the use of various fields of view during low-speed parking maneuvers by drivers with a rearview camera, a sensor system, a camera and sensor system combined, or neither technology. Participants performed four different low-speed parking maneuvers five times. Glances to different fields of view the second time through the four maneuvers were coded along with the glance locations at the onset of the audible warning from the sensor system and immediately after the warning for participants in the sensor and camera-plus-sensor conditions. Overall, the results suggest that information from cameras and/or sensor systems is used in place of mirrors and shoulder glances. Participants with a camera, sensor system, or both technologies looked over their shoulders significantly less than participants without technology. Participants with cameras (camera and camera-plus-sensor conditions) used their mirrors significantly less compared with participants without cameras (no-technology and sensor conditions). Participants in the camera-plus-sensor condition looked at the center console/camera display for a smaller percentage of the time during the low-speed maneuvers than participants in the camera condition and glanced more frequently to the center console/camera display immediately after the warning from the sensor system compared with the frequency of glances to this location at warning onset. Although this increase was not statistically significant, the pattern suggests that participants in the camera-plus-sensor condition may have used the warning as a cue to look at the camera display. The observed differences in glance behavior between study groups were illustrated by relating it to the visibility of a 12–15-month-old child-size object. These findings provide evidence that drivers adapt their glance behavior during low-speed parking maneuvers following extended use of rearview cameras and parking sensors, and suggest that other technologies which augment the driving task may do the same.